Approaches to a Dilemma During the Pandemic: Sequential Successes and Simultaneous Successes. Issue 1 (2nd January 2022) - Kim, Steven B.; Lee, Joonghak
Abstract : Since the breakout of the COVID-19 pandemic, many countries and local-level governments have made and adjusted decisions to control the movement of people. It is a dilemma because a decision from the perspective of public health and a decision from the perspective of economy (or freedom of people) are too distant on the spectrum of the level of restriction. Yet, some decision makers seek a compromising decision in order to succeed in both public health and economy. Under five assumptions with simple logistic models, we demonstrate hypothetical scenarios for the probability of simultaneous successes (both public health and economy) and the probability of simultaneous failures. The take-home messages are not surprising: We probably want to solve our pandemic crisis sequentially rather than simultaneously, and our responsible actions can lift the probability of simultaneous successes if we desperately need a compromising decision to solve it simultaneously.